Analisis Strategi Komunikasi Kiky Saputri Dalam Membangun Citra Diri di Media Sosial (@Kikysaputrii) - Euis Resti Nurmawandini; Anisti; Tuty Mutiah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Social media has become a strategic medium for shaping and strengthening the self- image of public figures. Kiky Saputri, a well-known Indonesian comedian and celebrity, utilizes her Instagram account to portray a humorous, genuine, and approachable persona to her followers. This study aims to analyze the communication strategies employed by Kiky Saputri in constructing her self-image on social media, particularly Instagram, using the theory of interpersonal communication by DeVito (2013) as the theoretical framework. This research uses a descriptive qualitative approach with data collected through in-depth interviews and documentation of social media activity. The findings reveal that the interpersonal communication strategies applied include openness, empathy, supportiveness, and equality in interactions, all of which contribute significantly to building a positive and authentic self-image in the public eye. These strategies also enhance follower engagement and reinforce Kiky Saputri’s position as a relatable and well-liked public figure. This study contributes to a deeper understanding of the role of interpersonal communication in managing self- image through social media platforms.